Performance and quality measurement of internet network services at muhammadiyah university of surakarta's faculty of health sciences with QOS parameter - Lathifah, Firasyana; Fadhil Musyaffa, Ariq (SHM Publisher, 2023)
In this fully digital age, a lot of individuals require an internet connection. A reliable network must be able to handle this need. Therefore, a stable network needs to establish and maintained correctly. A reliable internet connection is required at Muhammadiyah University of Surakarta's Faculty of Health Sciences to enhance student and lecturer activities in the educational process. This study will analyze the University of Muhammadiyah Surakarta's Faculty of Health Sciences internet network quality. Using Quality of Service (QOS) methods, the study estimated the quality performance of the existing network. The test measures the throughput, jitter, delay, and packet loss parameters using Wireshark. The result revealed that the Faculty of Health Sciences at University of Muhammadiyah Surakarta had a very good internet network, with a throughput value of 403.487 kbit/s with an index of 4 indicates an Outstanding category, a packet loss value of 6.2% with an index of 3 indicating a good category, a delay value of 16.691 ms with an index of 4 indicates an Outstanding category, and the last is the jitter value of 0.04913 ms with an index of 3 indicating an Outstanding category. Overall, the QoS value of internet network services at the Faculty of Health Sciences, University of Muhammadiyah Surakarta, is 3,5 or 87.5% in the satisfactory category.